2012
DOI: 10.4274/tjo.42.43265
|View full text |Cite
|
Sign up to set email alerts
|

Bilgisayar Kullanıcılarında Görülen Oküler Yüzey Değişikliklerinin Değerlendirilmesi

... ...

Abstract: ÖzetAmaç: Bu çalışmada bilgisayar kullanımına bağlı olarak ortaya çıkabilecek oküler yüzey değişikliklerinin değerlendirilmesi amaçlanmıştır. Ge reç ve Yön tem: Selçuk Üniversitesi Meram Tıp Fakültesinde sekreter olarak çalışan ve günlük bilgisayar kullanım süreleri en az 6 saat olan 40 gönüllü birey (Grup 1) ve bilgisayar kullanım süresi 6 saatin altında olan 50 sağlıklı birey (Grup 2) incelendi. Katılımcıların rutin göz muayenelerini takiben gözyaşı kırılma zamanı (GKZ) ölçüldü, anestezili ve anestezisiz Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Similarly, higher OSDI records were found in VDU users working for more than 8 hours in a dry eye evaluation study done by Gumus et al 20 Similar results were reported with significantly higher OSDI scores in those with 7-8 hours of computer use daily. [21][22][23] Similar finding has been reported in many studies. 24,25 In a study done among Japanese workers who used VDU for more than 8 hours per day had higher risk of Dry Eye Disease (OR=1.94; 95%CI,1.22-3.09, p=0.05).…”
Section: Resultssupporting
confidence: 89%
“…Similarly, higher OSDI records were found in VDU users working for more than 8 hours in a dry eye evaluation study done by Gumus et al 20 Similar results were reported with significantly higher OSDI scores in those with 7-8 hours of computer use daily. [21][22][23] Similar finding has been reported in many studies. 24,25 In a study done among Japanese workers who used VDU for more than 8 hours per day had higher risk of Dry Eye Disease (OR=1.94; 95%CI,1.22-3.09, p=0.05).…”
Section: Resultssupporting
confidence: 89%